2019
DOI: 10.3390/w11071403
|View full text |Cite
|
Sign up to set email alerts
|

Microturbines at Drinking Water Tanks Fed by Gravity Pipelines: A Method and Excel Tool for Maximizing Annual Energy Generation Based on Historical Tank Outflow Data

Abstract: Wherever the flow of water in a gravity pipeline is regulated by a pressure control valve, hydraulic energy in the form of water pressure can instead be converted into useful mechanical and electrical energy via a turbine. Two classes of potential turbine sites exist—those with (class 1, “buffered”) and those without (class 2, “non-buffered”) a storage tank that decouples inflow from outflow, allowing the inflow regime to be modified to better suit turbine operation. A new method and Excel tool (freely downloa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Different research projects have focused their investigation on energy recovery in pressurized water systems. One of the energy recoveries is through the application of PATs [14][15][16][17]. Williams et al [17] proposed substituting Pressure Reduction Valves (PRV) to recover the energy dissipated in the valves, generating significant electric savings.…”
Section: Pumps As Turbinesmentioning
confidence: 99%
“…Different research projects have focused their investigation on energy recovery in pressurized water systems. One of the energy recoveries is through the application of PATs [14][15][16][17]. Williams et al [17] proposed substituting Pressure Reduction Valves (PRV) to recover the energy dissipated in the valves, generating significant electric savings.…”
Section: Pumps As Turbinesmentioning
confidence: 99%
“…The literature review revealed no specific tool at the European level for even preliminary assessments for hydropower recovery in water networks. However, a slight exception can be made for a tool intended for water suppliers to perform the basic design of a site [34]. Some reviewed publications mentioned using standard Microsoft Excel calculations to complete a preliminary evaluation of water network sites; however, they are not openly available to hydropower designers.…”
Section: Introductionmentioning
confidence: 99%